2021
DOI: 10.1093/ofid/ofab464
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Epidemiology on a Public University Campus in Washington State

Abstract: Background We aimed to evaluate a testing program to facilitate control of SARS-CoV-2 transmission at a large university and measure spread in the university community using viral genome sequencing. Methods Our prospective longitudinal study used remote contactless enrollment, daily mobile symptom and exposure tracking, and self-swab sample collection. Individuals were tested if the participant was exposed to a known SARS-CoV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…If this was the case, we would expect to see vastly different patterns, particularly a higher frequency of B.1.1.304 and B.1.593 in nonstudents during November. Although there are differences in context, setting, and mitigation measures here compared with other IHE, this study suggests that previous findings with limited community surveillance may generalize more broadly [ 4 , 6 , 18 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…If this was the case, we would expect to see vastly different patterns, particularly a higher frequency of B.1.1.304 and B.1.593 in nonstudents during November. Although there are differences in context, setting, and mitigation measures here compared with other IHE, this study suggests that previous findings with limited community surveillance may generalize more broadly [ 4 , 6 , 18 ].…”
Section: Discussionmentioning
confidence: 71%
“…A seroprevalence study in Pennsylvania indicated that the community incidence of COVID-19 remained low throughout a period of high incidence in students [ 18 ]. Few or no viral descendants of student clusters in Dane County, Wisconsin, and Washington State have been detected in genomic surveillance of their respective communities with sampling density of 1%–3% [ 4 , 6 ]. One notable study from a university in the United Kingdom used genomic surveillance (8% of the community) and contact tracing to demonstrate separate viral lineages in university vs community cases [ 19 ].…”
mentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, university campuses have been sites of SARS-CoV-2 outbreaks 23 26 . Many universities provide free, convenient testing to facilitate SARS-CoV-2 surveillance within campus communities 23 , 25 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, university campuses have been sites of SARS-CoV-2 outbreaks 23 26 . Many universities provide free, convenient testing to facilitate SARS-CoV-2 surveillance within campus communities 23 , 25 , 27 . Using data collected from September 2021 to February 2022 through a campus testing program, we describe the rapid emergence of Omicron in a highly vaccinated university community and the clinical characteristics and transmission dynamics of the Omicron variant compared to the Delta variant.…”
Section: Introductionmentioning
confidence: 99%
“…Here we report the early identification of three initial introductions of an emerging lineage into a college campus, a high-risk population for SARS-CoV-2 spread (5,15,16) and emergence of travel-associated variants(4). The investigation benefited from available infrastructure for widescale asymptomatic testing and for genomic surveillance.…”
Section: Discussionmentioning
confidence: 99%